Saat Bicara Tidak Menyembuhkan: Laporan Kasus Pendekatan Umum Tatalaksana Depresi Pada Tuli - Lintuuran, Rivo Mario Warouw (Jurnal Locus Penelitian dan Pengabdian, 2025)
Depression is a common psychological problem in general population as well as in deaf community. Deaf with mental problems tend to face challenges not just stigma, but also lack of proper health care and a complex medical treatment. Very few studies in Indonesia focused on deaf and mental disorder. This case report described a 31 year old deaf female with depression. Since one year ago, she reported depressive symptoms such as low mood, anhedonia, feeling useless and anxious about her private life and work situation. Patient had minimal understanding of mental disorder and how to receive medical help which derived mostly from those who talk. This case report discussed a general approach in treating and several challenges in handling mental disorder in deaf individual especially psychopharmacological treatment and psychotherapy which needed verbal communication thus creating more complex approach from doctor who speaks to patient who used sign language. Using sign language interpreter may help patient and doctor creating therapeutic relationship and good outcome. Comprehensive understanding towards deaf with mental disorder may help the patient receiving adequate and equal service as general population.